Legal Implications of The Use of Permit to Open State Land as Collateral for Debt: A Case Study of Regional Regulation of Balikpapan City No. 1 of 2024 - Sari, Fitrizka Eka; Koeswahyono, Imam; Masykur, Hamidi (International Journal of Business, Law, and Education, 2023)
Indonesia is a country abundant in natural resources and human resources, aiming to provide prosperity for its people. The need for credit and the provision of credit facilities require collateral. The government has established a credit guarantee institution capable of providing legal certainty and legal protection. One of these institutions is the Mortgage Rights institution regulated by Law Number 4 of 1996 concerning Mortgage Rights on Land and Related Objects (UUHT). In the city of Balikpapan, East Kalimantan, there is a legal product in the field of land management based on regional autonomy, adhering to the principle of decentralization that grants authority through the enactment of Regional Regulation Number 1 of 2014 concerning State Land Opening Permits, known as "Izin Membuka Tanah Negara" (IMTN). IMTN is a permit granted by the Mayor or designated official to individuals or legal entities to open and/or utilize state-owned land directly controlled by the government. In this Regional Regulation, it is explicitly stated that IMTN cannot be used as collateral for debt transactions. However, in Balikpapan, there are still cooperatives or financing institutions that accept IMTN as collateral, binding it with a credit guarantee that is subsequently accompanied by an additional agreement known as "Surat Kuasa Membebankan Hak Tanggungan" (SKMHT). The existence of collateral with IMTN as the object is not permitted, as IMTN serves as administrative evidence for the initial proof of land rights ownership in Balikpapan. IMTN can later be processed to become land rights (Ownership Rights, Building Utilization Rights, Right to Use), which has led Notaries and Banks to accept IMTN as collateral.